Pemanfaatan Teknologi Informasi untuk Pemetaan Potensi Ekonomi dan Wisata di Desa Tema Tana - Lastri Susanti Bulu; Yulius Nahak Tetik; Maria Wilda Malo (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
This study aims to design and implement an information technology-based economic and tourism potential mapping system in Tema Tana Village. This village faces several problems, including manual data management, limited access to information, and the absence of an integrated system for efficiently presenting village potential data. This study uses a descriptive approach with data collection techniques through observation, interviews, and documentation studies. In developing the system, the Waterfall method is used, consisting of the stages of planning, design, implementation, and testing. The system design was carried out using the Unified Modeling Language (UML) to ensure a clear system structure and flow. The results of the system development indicate that the system is able to present information in the form of interactive digital maps and reports that are easily accessible to users. Testing using the Black Box Testing method shows that all system features function well and are in accordance with predetermined needs. Thus, this system is expected to improve the effectiveness of data management and support better decision-making processes in developing village potential, particularly in the economic and tourism sectors.